To Assess the Efficacy of Postoperative Antibiotics after Appendectomy in Patients with Non-Perforated Appendicitis - Govind Trivedi; Siddharth Mishra (Asian Journal of Medical Research, 2019)
Background: Appendicitis is the most common cause of acute abdominal pain, requiring surgical intervention and appendectomy is the most frequently performed emergency surgery. The present study was conducted to assess the efficacy of postoperative antibiotics after appendectomy in patients with non-perforated appendicitis.Subjects and Methods:The present study was conducted on 52 patients of appendectomy of both genders. Patients were divided into two groups. Group I patients did not receive post-operative antibiotic. Group II patients received postoperative antibiotic.Results:Age group 20-40 years had 12 patients in group I and 10 in group II, 40- 60 years had 9 in group I and 12 in group II and >60 years had 5 in group I and 4 in group II. The difference was non- significant (P> 0.05). SSI positive was seen in 11 in group I and 2 in group II, SSI negative was seen in 15 in group I and 24 in group II. The difference was significant (P< 0.05).Conclusion: Authors found that surgical site infection was relatively less in patients who received post operative antibiotics than those who did not receive antibiotics.